Innate Immunity in Wooless Lamb to Larvae of Amblyomma cajennense Tick (Fabricius, 1787) (Acari: Ixodidae) - Prosdocimi, C. C. [UNESP]; Bechara, Gervasio Henrique [UNESP]; Luduverio, D. J. [UNESP]; Otavio, F. M. S. [UNESP]; Del Vecchio, R. E. [UNESP] (Wiley-Blackwell, 2010)
P>The Cayenne tick Amblyomma cajennense infests preferably horses in its adult form but other mammal species in its immature stages and is the main vector of Rickettsia rickettsii, the Brazilian spotted fever pathogen. As wooless lambs are often raised on pasture together with horses, an experiment was performed to investigate their possible acquisition of resistance to A. cajennense after experimental infestations. Seven naive wooless lambs were infested thrice at 60 days interval with immature and adult instars of A. cajennense from a laboratory colony, the tick biotic potential being determined and biopsies of tick bite lesions taken to investigate the inflammatory cell component. Nearly 100% of larvae died in all infestations, while nymphs and adults fed normally throughout re-infestations. Microscopic features of adult tick bite lesions revealed predominance of neutrophils (38%) and eosinophils (36.8%), respectively, in the first and second infestations. In the third infestation, 43.6% of MN cells were found and about 31% of eosinophils. on the other hand, nymph bite lesions revealed in all infestations a predominance of eosinophils, increasing from 36% in the first infestation to 50.5% in the third one. It is concluded that wooless lambs present remarkable innate resistance against larvae of A. cajennense, but marked susceptibility to the other tick instars despite the migration of great number of eosinophils to the tick lesion.
Keywords: wooless lamb; Amblyomma cajennense; tick bite lesion; Inflammatory cells